P-145 Oral Administration of EGCG, a Green Tea Polyphenol, Both Suppresses and Rescues Mice from DSS-Induced Colitis. (March 2016) - Stillman, Andrew; Connors, Michael; Miller, Matthew; Qazzaz, Hassan; Dryden, Gerald
Abstract : Background: The anti-inflammatory effects of green tea polyphenols (GTP) have sparked considerable interest as a potential therapeutic agent for inflammatory bowel disease (IBD). We sought to evaluate the effects of orally administered (−)epigallocatechin-3-gallate (EGCG) on the dextran sulfate sodium (DSS) colitis model to determine whether this agent works as a potential preventive and/or treatment therapy for IBD. Methods: Groups (n = 5) of C57BL/6 mice were exposed to 2.5% DSS +/− EGCG in 2 or 20 μg/mL concentrations. Control groups were exposed to 2.5% DSS only from days 1 to 9, while EGCG was given as a preventive agent concurrently with DSS from days 1 to 9 or as a treatment agent after DSS administration on days 10 to 16. Animals were weighed daily, and colonoscopies were performed on days 9 and 16 to determine the endoscopic index of severity (EIS). Animals were sacrificed on day 17, and blood and colonic tissue samples were collected. Serum soluble cytokine analyses were performed using Milliplex multiplex assay. Tight junction protein analysis of colonic tissue was performed using Western blot. Results: Control animals developed significant weight loss and colitis by day 9 (EIS = 12). Animals that were given preventive doses of EGCG developed less severe colitis by day 9 (EIS = 5 and 4 for 2 and 20 μg/mL), while animals given treatment doses developed significant colitis by day 9 (EIS = 7 and 9 for 2 and 20 μg/mL) that resolved significantly, compared to control animals, by day 16 (EIS = 0.5 and 1 for 2 and 20 μg/mL). Additionally, preventive doses of EGCG protected animals from significant weight loss, another measure of colitis severity. Serum levels of pro-inflammatory cytokines (IL-6, IFN-γ, and IL-12) were significantly lower in all preventive and treated animals than control animals. Western blot analysis of tight junction protein expressions showed the following modulations by preventive and treatment doses of 20 μg/mL EGCG, respectively (with 100% equal to protein expression in control animals): occludin, 195.7% and 216.2%; claudin-1, 229.2% and 438.7%; claudin-4, 67.2% and 62.4%; and ZO-1, 163.2% and 181.8%. Conclusions: Oral administration of EGCG protected against weight loss and severe colitis when used in a preventive capacity; moreover, EGCG treatment was effective at rapidly resolving colitis. Furthermore, EGCG administration markedly attenuated pro-inflammatory cytokine response and reinforced tight junction integrity. These data provide further evidence supporting the use of EGCG for treating inflammatory bowel disease and for the anti-inflammatory mechanism that we have seen in IBD patients and models.